MENTORING OF MBKM STUDENTS AS A CATALYST FOR HUMAN RESOURCE DEVELOPMENT OF MSMES IN PALU CITY - Alam Surahman Cakmar; Niluh Putu Evvy Rossanty; Yoberth Kornelius; Mohammad Ega Nugraha (RADJA PUBLIKA, 2025)
This study aims to analyze the role of student mentoring in the Merdeka Belajar Kampus Merdeka (MBKM) program as a catalyst for human resource development for MSMEs in Palu City. The research method used was qualitative with a descriptive approach, involving field supervisors (DPL), student mentors, and MSME actors as samples. Data were collected through interviews with nine informants and analyzed using triangulation techniques and Nvivo 15 software. The results show that DPL plays a crucial role as a bridge between students and MSMEs, not only as academic mentors but also as motivators and facilitators in shaping students' mindsets and practical skills. This mentoring provides opportunities for students to develop relevant soft and hard skills. However, there are obstacles in the form of the lack of clear achievement standards and success indicators in the mentoring program, so that the progress of MSMEs during mentoring does not always show significant improvement. These findings emphasize the need to develop concrete and measurable output standards to increase the effectiveness of the MBKM program.